2008
DOI: 10.2495/wm080801
|View full text |Cite
|
Sign up to set email alerts
|

Potentiometric biosensor for acrylamide determination in wastewater using wild type amidase fromPseudomonas aeruginosa

Abstract: Acrylamide is a toxic amide with potentially hazardous effects on the environment and human health. This paper reports the results regarding the development of a potentiometric biosensor in order to determine the amount of this amide in wastewater samples. The biosystem consisted of whole cells of Pseudomonas aeruginosa containing intracellular amidase activity which hydrolyses acrylamide producing ammonium ion and acrylic acid. The cells were immobilized on the surface of several types of membranes such as po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Lab experiments conducted in ideal conditions, especially those that tested artificially prepared samples, would require further testing of biosensors for direct use in wastewater and sewage systems. While papers often cited that maintenance needs of biosensors were less intensive than current methods, smart toilets and other sensors often require regular cleaning [ 31 , 41 ]. One paper specifically states that, “Most of the bacterial biosensors that are currently available are large, require electronics or are too complicated to operate in [developing] countries” [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lab experiments conducted in ideal conditions, especially those that tested artificially prepared samples, would require further testing of biosensors for direct use in wastewater and sewage systems. While papers often cited that maintenance needs of biosensors were less intensive than current methods, smart toilets and other sensors often require regular cleaning [ 31 , 41 ]. One paper specifically states that, “Most of the bacterial biosensors that are currently available are large, require electronics or are too complicated to operate in [developing] countries” [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tests with real industrial effluents demonstrated efficient substrate recovery, reinforcing the utility of the biosensor in monitoring wastewater quality and industrial pollution control, with a focus on applying electrochemical methods for precise and efficient detection. 78 However, despite the successful immobilization strategy of Pseudomonas cells leading to a biosensor with a good response time and remarkable sensitivity, there is a concern about potential premature cell loss, a longer device half-life, and better storage resistance of the membrane.…”
Section: Aptasensorsmentioning
confidence: 99%